2015
DOI: 10.3390/molecules200915572
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Cytotoxic Activity against HepG-2 Cells of Naphthoquinones from Green Walnut Husks of Juglans mandshurica Maxim

Abstract: Twenty-seven naphthoquinones and their derivatives, including four new naphthalenyl glucosides and twenty-three known compounds, were isolated from green walnut husks, which came from Juglans mandshurica Maxim. The structures of four new naphthalenyl glucosides were elucidated based on extensive spectroscopic analyses. All of these compounds were evaluated for their cytotoxic activities against the growth of human cancer cells lines HepG-2 by MTT [3-(4,5-dimethylthiazo l-2-yl)-2,5 diphenyl tetrazolium bromide]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 24 publications
4
37
0
4
Order By: Relevance
“…Compound 11 (peak 11 in Figure 2 B): ESI-MS ( m / z ): 163 [M + H] + , molecular formula C 10 H 10 O 2 , M = 162; 1 H-NMR (CD 3 OD- d 6 , 600 MHz) δ: 2.65 (1H, ddd, J = 5.4, 2.4, 5.4 Hz, H-2), 2.88 (1H, ddd, J = 3.0, 6.0, 3.0 Hz, H-2), 2.15 (1H, m, H-3), 2.38 (1H, m, H-3), 4.94 (1H, dd, J = 4.2, 4.2 Hz, H-4), 7.65 (2H, m, H-5, 6), 7.44 (1H, m, H-7), 7.97 (1H, d, J = 7.8 Hz, H-8); 13 C-NMR (CD 3 OD- d 6 , 150 MHz) δ: 198.5 (C-1), 146.5 (C-10), 133.8 (C-6), 130.9 (C-9), 127.6 (C-8), 127.1 (C-7), 126.2 (C-5), 66.9 (C-4), 34.9 (C-2), 31.7 (C-3). Comparing the above data with the literature [ 32 ], compound 11 was identified as (4 S )-4-hydroxy-1-tetralone.…”
Section: Methodssupporting
confidence: 56%
“…Compound 11 (peak 11 in Figure 2 B): ESI-MS ( m / z ): 163 [M + H] + , molecular formula C 10 H 10 O 2 , M = 162; 1 H-NMR (CD 3 OD- d 6 , 600 MHz) δ: 2.65 (1H, ddd, J = 5.4, 2.4, 5.4 Hz, H-2), 2.88 (1H, ddd, J = 3.0, 6.0, 3.0 Hz, H-2), 2.15 (1H, m, H-3), 2.38 (1H, m, H-3), 4.94 (1H, dd, J = 4.2, 4.2 Hz, H-4), 7.65 (2H, m, H-5, 6), 7.44 (1H, m, H-7), 7.97 (1H, d, J = 7.8 Hz, H-8); 13 C-NMR (CD 3 OD- d 6 , 150 MHz) δ: 198.5 (C-1), 146.5 (C-10), 133.8 (C-6), 130.9 (C-9), 127.6 (C-8), 127.1 (C-7), 126.2 (C-5), 66.9 (C-4), 34.9 (C-2), 31.7 (C-3). Comparing the above data with the literature [ 32 ], compound 11 was identified as (4 S )-4-hydroxy-1-tetralone.…”
Section: Methodssupporting
confidence: 56%
“…Peaks 4, 13 and 16 correspond to naphthalene derivatives. This group of molecules was already identified in J. mandshurica fruits (Jin-Hai et al, 2018), husks (Jin-Hai et al, 2018;Zhou et al, 2015) and branches (Wang et al, 2017). As with tetralone derivatives, natural naphthalene also occurs with hydroxyl, hexosyl and hydroxybenzoyl substitutions (Sun et al, 2012).…”
Section: Phytochemical Composition Of Walnut Husksmentioning
confidence: 73%
“…(Du et al, 2014;Li et al, 2013Li et al, , 2008aLiu et al, 2010;Talapatra et al, 1988;Wang et al, 2017). Particularly, the tetralone derivatives found in green husks of J. regia usually occur as hydroxyl, hexosyl and hydroxybenzoyl derivatives, with several isomeric alternatives (Zhou et al, 2015). Wang et al (2017), the compounds were identified as tetralone galloyl hexoside derivatives, specifically, dihydroxytetralone galloyl hexoside isomers (peaks 8 and 9) and trihydroxytetralone galloyl hexoside (peak 10).…”
Section: Phytochemical Composition Of Walnut Husksmentioning
confidence: 99%
See 2 more Smart Citations